When the Baby Cries at Night: Inelastic Buyers in Non-Competitive Markets - Giacomo Calzolari; Andrea Ichino; Francesco Manaresi; Viki Nellas (Institute for the Study of Labor (IZA), 2014)
We investigate empirically how sellers react to changes in the population of their consumers, identifying the effects of demand composition and demand size with limited information on costs. We show how pharmacists in Italy selectively increase the price of some products when they observe in their cities an exogenous influx of parents of newborns, conceivably less elastic buyers as compared with other more experienced and less pressed consumers. Exploiting population based laws that fix the number of pharmacies in a city, we use RDD to measure the effect of competition on sellers' ability to extract surplus from less elastic buyers.
Keywords: D43; D83; L13; 330; demand elasticity; consumer's information; price competition; pharmacies; regression discontinuity